KEBIJAKAN FISKAL DI INDONESIA DALAM PERSPEKTIF ISLAM - Yulia Leni Fitria Sari; Stevia Yolanda, Heru Saputra, Mutia Rani (Jurnal Ekonomi dan Bisnis, 2024)
Fiscal policy is a step that influences a country's budget demand and spending. The aim is to maintain stability and improve welfare for society and in accordance with Maqasib Syariah. The aim of this research is to analyze the conformity of Fiscal Policy in Indonesia with sharia principles. This research uses a qualitative approach based on descriptive analysis techniques such as writings and data sourced from various journals, books related to Islamic principles and fiscal policy in Indonesia. The research results show that fiscal policy in Indonesia is based on Islamic principles but is not comprehensive because in Indonesia there are policies related to taxes on alcoholic drinks such as alcohol. For this reason, it is hoped that the government will better adjust policies related to taxes in accordance with the rules of Islamic law.